Design and synthesis of a photocleavable biotinylated nucleotide for DNA analysis by mass spectrometry - Bai, Xiaopeng (Oxford University Press, 2004)
We report here the design, synthesis and evaluation of a novel photocleavable (PC) biotinylated nucleotide analog, dUTP-PC-Biotin, for DNA polymerase extension reaction to isolate DNA products for mass spectrometry (MS) analysis. This nucleotide analog has a biotin moiety attached to the 5-position of 2′-deoxyribouridine 5′-triphosphate via a photocleavable 2-nitrobenzyl linker. We have demonstrated that dUTP-PC-Biotin can be faithfully incorporated by the DNA polymerase Thermo Sequenase into the growing DNA strand in a DNA polymerase extension reaction and that its incorporation does not hinder the addition of the subsequent nucleotide. Therefore, the DNA extension fragments generated by using the dUTP-PC-Biotin can be efficiently isolated by a streptavidin-coated surface and recovered by near-UV light irradiation at room temperature in mild condition for further analysis without using any chemicals or heat. Single and multiple primer extension reactions were performed using the dUTP-PC-Biotin to generate DNA products for MALDI-TOF MS analysis. Such nucleotide analogs that carry a biotin and a photocleavable linker will allow the isolation and purification of DNA products under mild conditions for MS-based genetic analysis by DNA sequencing or multiplex single nucleotide polymorphism (SNP) detection. Furthermore, these nucleotide analogs should also be useful in isolating DNA–protein complexes under non-denaturing conditions.